DIRECTIONS FOR DEVELOPING TOURISM ACTIVITY THROUGH IMPROVING THE TAX SYSTEM (American Journal of Business Management, Economics and Banking, 2024)
The directions of development of tourism activity through improvement of the tax system were considered. The calculation of losses to the budget under the AOS in 2022 as a result of reducing the turnover tax rate to 1 percent was analyzed. The dynamics of forecast values of the main economic indicators of the tourism sector for 2024-2030 were presented.